Have outcomes following extremely preterm birth improved over time?. Issue 3 (June 2020) - Cheong, Jeanie LY.; Spittle, Alicia J.; Burnett, Alice C.; Anderson, Peter J.; Doyle, Lex W.
Abstract: Increased survival of infants born preterm, especially those born extremely preterm (<28 weeks' gestation), has meant that more are reaching later childhood and adulthood. As preterm birth is associated with a higher risk of neurodevelopmental deficits, the aim of this review was to determine whether or not the advances in perinatal care that led to improved survival have also had a positive impact on long-term neurodevelopment. Studies examining temporal changes in neurodevelopment are limited, and only from high-income countries. However, based on available published data, there is no definite trend of improved neurodevelopment at school age for neurosensory, cognitive, academic achievement, motor or executive function with time. Cerebral palsy rates, however, may be decreasing. More research is needed into the potential contributors for the trends observed, and also for other outcomes such as mental health and behavior.